Analisis Yuridis Keabsahan Jual Beli Voucher Game Online oleh Anak di Bawah Umur - Ammanawwara, Ammanawwara; Azwar, Tengku Keizerina Devi; Sukarja, Detania; Leviza, Jelly (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
This article analyzes the regulation of online game access in Indonesia, the validity of purchasing game vouchers by minors, both conventionally and electronically, and the urgency of legal protection in the acquisition of such vouchers by underage individuals. The research method employed is juridical normative, utilizing secondary data, focused on written regulations, legal principles, legal systematics, legal comparisons, and legal history. The findings reveal that Minister of Communication and Information Regulation No. 11 of 2016 governs online game access through the Indonesian Game Rating System (IGRS), categorizing users into four age groups. Purchasing game vouchers by minors is legally permissible but becomes invalid when breaching age or moral requirements and relevant laws. Legal protection necessitates regulations concerning age limits and transactional competency, especially within retail establishments offering game vouchers, to prevent adverse implications of online game usage among children.